EFFECT OF SUPPLEMENTATION FENUGREEK OIL TO THE DIET ON THE PHYSIOLOGICAL, ANATOMICAL AND HISTOLOGICAL TRAITS OF BROILERS - Hasanain N. Ezzat (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to evaluate the effect of supplementing fenugreek seed oil to the diet on the physiological, anatomical and histological characteristics of broilers. A total of 200 chicks one day-old of (Ross308) were used in this study and divided into 4 treatments, 5 replicate for each treatment by 10 chicks in each replicate. The treatments were T1(control diet) = without additives (basal diet), T2 = basal diet + 0.25 ml fenugreek oil / kg, T3 = basal diet + 0.50 ml fenugreek oil / kg and T4 = basal diet + 0.75 ml fenugreek oil /kg. The results showed Fenugreek oil inclusion at levels 0.50 ml/kg exhibited significant decrease (P <0.05) in jejunum and ileum relative weight, villi height and increasing (P <0.05) heart relative weight for T3 compare with the other groups. T4 showed significant increased (P <0.05) in lactic acid bacteria count compare with control group (T1). Supplemented 0.25 ml/ kg of fenugreek oil resulted in increasing villi height, thickness and Epithelium thickness for duodenum as compared with control group. It was observed that adding 0.25 ml/kg and 0.50 ml/kg feed fenugreek oil to the broiler chicken diet could be optimum level to enhance the productivity and histological characteristics of broiler.